The convolution product of the derivative of the Dirac delta 1-x2 - García, M; Aguirre, M (Nexo Revista Científica, 2010)
In this paper we give a sense to distribution convolution product of δ (k-1) (1- x2)∗δ (l-1) (1- x2). As a particular case we obtain a formula to convolution product of δ (1- x2)∗δ (1- x2) (C.f. formula (38)). Keywords: Convolution; Product. DOI: 10.5377/nexo.v22i2.45 Nexo Revista Científica Vol. 22, No. 02, pp.66-71/Diciembre 2009